Did Dōgen go to China? - Heine, Steven (Oxford University Press, 2006)
Dogen (1200-1253), the founder of the S?t? Zen sect in Japan, is especially known for introducing to Japanese Buddhism many of the texts and practices that he discovered in China. Heine reconstructs the context of D?gen's travels to and reflections on China by means of a critical look at traditional sources both by and about D?gen in light of recent Japanese scholarship. While many studies emphasize the unique features of D?gen's Japanese influences, this book calls attention to the way Chinese and Japanese elements were fused in D?gen's religious vision. It reveals many new materials and insights into Dogen's main writings, including the multiple editions of the Sh?b?genz?, and how and when this seminal text was created by Dogen and was edited and interpreted by his disciples. This book is the culmination of the author's thirty years of research on Dogen and provides the reader with a comprehensive approach to the master's life works and an understanding of the overall career trajectory of one of the most important figures in the history of Buddhism and Asian religious thought